Does leader’s emotional intelligence influence subordinates’ task performance, subordinates’ organizational citizenship behaviour and organizational culture - Aziz, Faiq; Md Rami, Ahmad Aizuddin; Mahadi, Nomahaza (Innovare Academics Sciences, 2020)
Leadership and emotional intelligence are important approaches need to be addressed by an organization because they are able to project positive impact in the organizational context. Organizations worldwide is now demanding for potential leaders that have extraordinary qualities to manage and lead them towards exceptional success. An emotionally intelligent leader is seen to be a potential person to connect the members in the organization and delivers tasks towards achieving organizational objectives. This research employs a quantitative research methodology to explore the factors influence the relationship between leader’s emotional intelligence (EI) with subordinates’ task performance (STP), subordinates’ organizational citizenship behaviour (SOCB) and organizational culture (OC) in private services sector in Malaysia. Data has been collected from 150 employees working in private services sector to see their evaluation towards their leader’s emotional intelligence (EI) based on the factors; STP, SOCB and OC. The result shows that the relationship between the variables are strong and positively related to each other.